2021
DOI: 10.1088/1755-1315/884/1/012024
|View full text |Cite
|
Sign up to set email alerts
|

Constructing Student’s Physical Preparedness through Game-Based Activities in Disaster-Safe School

Abstract: Indonesia is a country that has great potential for disaster. A major earthquake hit the Special Region of Yogyakarta, especially Bantul Regency, in 2006. This has demanded the establishment of a disaster-safe school that is ready to anticipate disasters. Disaster-safe school students need to be fully prepared in various aspects, including physical aspect. Therefore, this study aims to determine the increase in physical fitness before and after carrying out game-based physical activities for upper grade studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…This inadvertently led to a decrease in the effectiveness of practical training, crucial for physical education teacher students. The decline in physical preparedness of university students was highlighted in the studies by Nopembri et al [6] and Franks et al [7]. The authors emphasize the importance of teacher education programs in the context of students' physical readiness to face various emergency situations.…”
Section: Introductionmentioning
confidence: 99%
“…This inadvertently led to a decrease in the effectiveness of practical training, crucial for physical education teacher students. The decline in physical preparedness of university students was highlighted in the studies by Nopembri et al [6] and Franks et al [7]. The authors emphasize the importance of teacher education programs in the context of students' physical readiness to face various emergency situations.…”
Section: Introductionmentioning
confidence: 99%
“…One of the factors influencing basic motor skills is regular physical activities [15]. Doing regular physical activities with the correct motions is considered to improve the organ functions of a body and fitness [16]. Previous studies revealed that fitter children had better academic performance than the less fit children [4,17].…”
Section: Introductionmentioning
confidence: 99%